ANALISA PENGARUH STORE CORPORATE IMAGE DAN CUSTOMER SATISFACTION TERHADAP STORE PERFORMANCE PADA USAHA RETAIL BAHAN BANGUNAN DAN PERLENGKAPAN RUMAH TANGGA DI SURABAYA - Soetanto, Fransisca (Business Accounting Review, 2015)
The purpose of this study was to examine the affect of corporate image on store storeâs performance through customerâs satisfaction as the intervening variable on retail store building materials and home appliances in Surabaya. Sample of this study is 35 retail stores of building materials and home appliances in Surabaya. Data were collected by distributing questionnaire to the customers and managers of the stores. This study were used path modeling analysis technique with PLS. Results showed that there were positive and significant affect of store Â corporate image on customer satisfaction, positive and significant affect of customer satisfaction on store performance, and also positive and significant affect of corporate image on store performance on retail store building materials and home appliances in Surabaya.